Long-term prognosis in left ventricular non-compaction cardiomyopathy. (3rd October 2022) - Guerra, F; Barbarossa, A; Alfieri, M; Paolini, F; Stronati, G; Ciliberti, G; Torselletti, L; Coretti, F; Coraducci, F; Belleggia, S; Principi, S; Silenzi, M; et al.
Abstract: Introduction: Left ventricular non compaction (LVNC) cardiomyopathy is an often underdiagnosed disease characterized by a thickened myocardium with a two-layered structure. Clinical presentations are very variable, ranging from an apparent lack of functional anomalies to heart failure, ventricular arrhythmias and, in some cases, even ischaemic stroke. Despite great improvements in diagnostic performance, there is still a wide lack of evidence regarding prognosis and management of affected patients. Purpose: The aim of the present study was to investigate predictors of cardiovascular death or cardiovascular-related hospitalization in patients with LVNC over a long-term follow-up. Methods: All consecutive patients with a definite diagnosis of LVNC admitted to the Cardiomyopathy Clinic of our institution from Jan 2015 to Dec 2020 were consecutively enrolled. Inclusion criteria were an age ≥18 years old and a diagnosis of LVNC made either by MRI or echocardiography. Exclusion criteria were a life expectancy ≤1 year and the inability to express informed consent for the study. All patients were follwed-up every six months. The primary endpoint was a composite of cardiovascular death and unplanned cardiovascular hospitalization. Results: Twenty-one patients (14 male, age 40±17 years) meeting the inclusion criteria were prospectively enrolled and followed-up for a median of five years. LVNC patients with a previous history of supraventricular tachycardia at the time of diagnosis are more likely to meet the primary composite endpoint during follow-up (60% vs. 18%; p=0.048; Figure 1). On the other hand, neither LVEF (measured either with echo or CMR) nor functional status were associated with a significantly increased risk of the composite endpoint (all p=NS). Other significant predictors of increased risk include history of OSAS (z2 = 4.158), active/previous smoking (z2 = 6.279), and ST-segment alterations (z2 = 4.158). NC/C, as measured by either echo or CMR, was not a predictor of cardiovascular events (HR 0.18; 95% CI 0.31–1.08; p=NS). Conclusions: Our data show how, in patients with LVNC, supraventricular tachycardias are related to worse outcomes and their presence should prompt a closer follow-up in order to detect possible adverse events. ST-segment alterations, OSAS and smoking are also related to a poorer prognosis, but their relevance should be further assessed. Surprisingly, in our sample LVEF and NC/C ratio were not predictors of worse outcomes; the reason might be that in LVNC patients mortality and cardiovascular hospitalizations resemble complex genetic and molecular mechanisms that differentiate them from other cardiomyopathies, but the paucity of the population prevents us from making wider inferences. Funding Acknowledgement: Type of funding sources: None.